Optimalisasi program perkesmas dengan kunjungan rumah terhadap tingkat kemandirian keluarga serta peningkatan pengetahuan perawat dalam penulisan askep keluarga - Milya Novera; Meta Rikandi; Mandria Yundelfa; Rika Syafitri (Universitas 'Aisyiyah Yogyakarta, 2021)
Program Indonesia Sehat Pendekatan Keluarga (PISPK) is necessary to have continuous intervention and become a integrated program at the Public Health Center (Puskesmas). The aim purposes of this activities was to analyzed The desired objectives are to optimize home visits to increase the level of family independence and to optimize the competence of nurses in writing and documentation of family nursing care plan integrated with Nanda, Noc and Nic. The implementation phase includes home visits conducted 2-4 times and carrying out cross-program activities and the evaluation phase includes recompiling and analyzed data. There are 18 heads of households who are respondents. This activity showed that home visits through providing family nursing care and education in the family gave change the family independence level. In the future, it is expected that home visits will become priority of Public Health Center (Puskesmas) activities to improve community health status, In addition, the guidelines and modules are able to increase the knowledge, attitudes, skills, and activities of nurses in the implementation of community health services which increase the use of health facilities by families and as a complement to the community health services module in order to improve the performance of Nurse in Public Health center.